Trends in absolute income mobility in North America and Europe - Robert Manduca; Maximilian Hell; Adrian Adermon; Jo Blanden; Espen Bratberg; Anne C. Gielen; Hans van Kipepersluis; Keun Bok Lee; Stephen Machin; Martin D. Munk; Martin Nybom; Yuri Ostrovsky; et al. (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
We compute rates of absolute upward income mobility for the 1960-1987 birth cohorts in eight countries in North America and Europe. Rates and trends in absolute mobility varied dramatically across countries during this period: the US and Canada saw upward mobility rates near 50% for recent cohorts, while countries like Norway and Finland saw sustained rates above 70%. Decomposition analysis suggests that differences in the marginal income distributions, especially the amount of cross-cohort income inequality, were the primary driver of differing mobility rates across countries. We also demonstrate that absolute mobility rates can be accurately estimated without linked parent-child data.
Keywords: J62; 330; Intergenerational mobility; absolute mobility; inequality